PENGEMBANGAN APLIKASI SISTEM INFORMASI REPOSITORI KARYA ILMIAH PADA STMIK PRABUMULIH - Andi Christian; Muchlis Muchlis (Paradigma, 2020)
The rapid development of Information Technology in the current era of globalization has become a fundamental need in supporting the effectiveness and quality of the education process. The Repository Information System is a place for processing and archiving data of scientific work in educational institutions. This scientific information system repository application was developed based on web site technology that is responsive to mobile software, it is hoped that with the development of this repository information system, young students can look for references. In developing an information system repository of scientific works using the Waterfall Method which is a method of developing information systems design systematically through predetermined stages. It is hoped that by developing information systems to manage scientific repositories, this scientific work can handle the scientific management problems of students and lecturers so that scientific work can be carried out effectively and efficiently.